Fate of Planktonic and Biofilm-Derived Listeria monocytogenes on Unwaxed Apples during Air and Controlled Atmosphere Storage - Natasha Sloniker; Ourania Raftopoulou; Yi Chen; Elliot T. Ryser; Randy Beaudry (Foods, 2023)
Multiple recalls and outbreaks involving Listeria monocytogenes-contaminated apples have been linked to the post-harvest packing environment where this pathogen can persist in biofilms. Therefore, this study assessed L. monocytogenes survival on apples as affected by harvest year, apple cultivar, storage atmosphere, and growth conditions. Unwaxed Gala, Granny Smith, and Honeycrisp apples were dip-inoculated in an 8-strain L. monocytogenes cocktail of planktonic- or biofilm-grown cells (~6.5 log CFU/mL), dried, and then examined for numbers of L. monocytogenes during air or controlled atmosphere (CA) (1.5% O2, 1.5% CO2) storage at 2 °C. After 90 days, air or CA storage yielded similar L. monocytogenes survival (p > 0.05), regardless of harvest year. Populations gradually decreased with L. monocytogenes quantifiable in most samples after 7 months. Apple cultivar significantly impacted L. monocytogenes survival (p < 0.05) during both harvest years with greater reductions (p < 0.05) seen on Gala compared to Granny Smith and Honeycrisp. Biofilm-derived cells survived longer (p < 0.05) on L. monocytogenes-inoculated Gala and Honeycrisp apples compared to cells grown planktonically. These findings should aid in the development of improved L. monocytogenes intervention strategies for apple growers and packers.